P-021 Interim safety and occlusion outcomes of endovascular treatment of very small intracranial aneurysms in the sterling registry. (23rd July 2022) - Jankowitz, B; De Leacy, R; Puri, A; Starke, R; Yoo, A; Gariel, F; Jahshan, S; Kulcsar, Z; Schirmer, C; Chivot, C; Howington, J; Pero, G; et al.
Abstract : Introduction: There are no established guidelines and considerable differences in practice patterns in the treatment of very small intracranial aneurysms. We present real-world safety and occlusion outcomes of endovascular treatment of very small aneurysms with Galaxy and MicrusFrame coils from the STERLING registry. Materials and Methods: STERLING (NCT03642639 ) is a prospective, global, real-world registry of brain aneurysm treatment with Galaxy and MicrusFrame coils (Cerenovus, Irvine, CA). Very small (<4 mm) intracranial aneurysms and all other aneurysms (≥4 mm) with available core lab imaging data from STERLING were included in this interim analysis. Results: Target aneurysms in STERLING ranged in size from 2.40 to 31.30 mm. Twenty-four very small and 375 other aneurysms were identified, with an average maximum diameter of 3.67 ± 0.490 mm and 7.42 ± 3.295 mm, respectively. Aneurysm characteristics and treatment outcomes are compared in table 1 . Notable differences included lower age and lower percentage of females in the very small aneurysm cohort. Treatment of very small aneurysms required shorter procedure (1.44 ± 0.621 vs. 1.70 ± 1.220 hours) and less total fluoroscopy time (40.3 ± 15.34 vs. 47.2 ± 27.30 min), although the hospital stay was longer (8.8 ± 8.65 vs. 7.5 ± 7.17 days). Mean packing density in the <4 mm cohort was 34.2 ± 17.65%. Complete and adequate occlusion (modified Raymond-Roy I and I or II) rates for the very small aneurysms were 66.7% (16/24) and 87.5% (21/24) post procedure, 88.9% (8/9) complete and adequate at 6 months, and 75% (3/4) complete and 100.0% (4/4) adequate occlusion at the 1-year follow up, with a 100% (5/5) good mRS at 1 year for unruptured cases. There were no procedural complications and no device-related SAEs though a 1.5 year follow up. There are no retreatments in the very small aneurysms. Comparative results for the ≥4 mm cohort are included in table 1 . Conclusion: Very small aneurysms, ranging in size from 2.40 to 3.90 mm, constituted 6% (24/399) of the STERLING registry cases included in this interim analysis. Treatment with Galaxy and MicrusFrame coils showed very high rates of adequate occlusion and good clinical outcome, with no retreatments and an excellent safety profile. Disclosures: B. Jankowitz: 2; C; Stryker, Medtronic. 6; C; Medtronic. R. De Leacy: 2; C; Imperative Care, Cerenovus, Siemens Healthineers, Stryker Neurovascular, Penumbra. 4; C; Synchron, Endostream, Q'Apel Medical, Spartan Micro, Vastrax. A. Puri: 1; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus. 2; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus, Microvention, Agile, Merit Medical, Corindus, Q'Apel, Arsenal Medical, Imperative Care, Perfuze Medical. 4; C; InNeuroCo Inc, Galaxy Therapeutics, Agile Medical, Perfuze Medical, NTI. R. Starke: 1; C; NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, NIH, Medtronic. 2; C; Medtronic, Penumbra, Abbott, InNeuroCo, Cerenovus. 6; C; Medtronic, Penumbra, Abbott, InNeuroCo, Cerenovus. A. Yoo: 1; C; Medtronic, Cerenovus, Penumbra. 2; C; Penumbra, Cerenovus. 4; C; Insera Therapeutics. F. Gariel: 2; C; Qynapse. S. Jahshan: None. Z. Kulcsar: None. C. Schirmer: 1; C; Penumbra. 4; C; Neurotechnology Investors. C. Chivot: None. J. Howington: 6; C; Chemence Medical. G. Pero: None. T. Yao: 2; C; Medtronic. 6; C; Medtronic, Microvention. A. Polifka: 2; C; Depuy Synthes. A. Evans: None. O. Zaidat: 1; C; Stryker, Medtronic, Cerenovus, Penumbra, Genentech. 2; C; Cerenovus, Stryker, Penumbra, Medtronic, Neuravi, NIH StrokeNet, Codman. 3; C; Cerenovus, Stryker, Penumbra, Medtronic. 4; C; Galaxy Therapeutics LLC. 6; C; NIH, Codman, Stryker, Penumbra, Medtronic Neurovascular.